REVEALING THEME OF THE ROAD NOT TAKEN BY ROBERT FROST - Sri Mulyati (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Literature is expressions of artistic and imaginative facts as manifestation human life, through language which as media which has good efects towards human life. Literature is a form of creative works which has obejcts human and their living used language as a media. Literature is art activities that has signs as the tool and imaginative.The writer analyzed a poetry by Robert Frost “ The Road Not Taken”. This poetry published in 1916 and became the most famoaus poetry of frost. The analysis focuses on the theme of the poetry. This poetry inspired by real story of frost friend, Thomas Thompson.The theme of this poetry describes about a deep regret of the speaker, because he had made the wrong choice and didn’t take the other road. At first, he thought that the divergent choices were equally same, that is would end goods. The choice he made got him killed two years later at the battle of Arrasafter  he gave the copy of his poetry